Effect of changes in population density and crop productivity on farm households in Malawi - Komarek, Adam M.; Msangi, Siwa (International Association of Agricultural Economists, 2019)
This study examines the ex‐ante farm‐household effects of changes in family size, yield potential, and yield gaps using a farm‐household simulation model that reflects the economic and biophysical conditions of central Malawi. Disparities between growth in human population and crop yields present challenges for farm‐household crop production and income in sub‐Saharan Africa. We focus on the effect of growth in yield potential and a more efficient use of livestock manure as approaches to improving crop production and incomes in the face of looming population pressures. Our results suggest that, even without considering climate change, expected changes in population density and crop prices in 2050 mean that per person crop production and income may fall by 21% compared to 2013 values if yield potential and yield gaps remain constant. However, per person crop production and income could increase in 2050 by 8% compared to 2013 values if (1) growth rates of yield potential rise for maize by 1.13% each year and for legumes rise by at least 0.4% each year, and (2) farmers use livestock manure more efficiently. Our foresight approach to considering crop production at the farm‐household scale supplements macro‐scale analyses of the production dimension of food security.